2015
DOI: 10.1007/s40719-015-0010-2
|View full text |Cite
|
Sign up to set email alerts
|

Penetrating Injuries to the Stomach, Duodenum, and Small Bowel

Abstract: Since operative management became the standard for hollow viscus injury, the techniques regarding the identification and subsequent repair of injuries to the stomach, small intestine, and duodenum have remained relatively unchanged. In this manuscript, we describe the contemporary management of penetrating hollow viscus injury as practiced at the Elvis Presley Memorial Trauma Center in Memphis, Tennessee. We commence with the general principles of laparotomy for trauma, followed by specific discussion of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…Such perforations invariably cause pneumoperitoneum. 7 The present case had no pneumoperitoneum even with moderate sized gastric perforation. This could probably be due to the anterior gastric tear being occluded by solid food material preventing the escape of air into peritoneal cavity.…”
Section: Discussionmentioning
confidence: 43%
“…Such perforations invariably cause pneumoperitoneum. 7 The present case had no pneumoperitoneum even with moderate sized gastric perforation. This could probably be due to the anterior gastric tear being occluded by solid food material preventing the escape of air into peritoneal cavity.…”
Section: Discussionmentioning
confidence: 43%
“…Once these goals have been achieved, the patient’s tendency towards the lethal diamond should be corrected and only then can the temporized injuries be managed definitively. A recent Cochrane review found that Damage Control Surgery patient selection is heavily dependent on clinical judgment and although it certainly has improved survival in the severely injured, it has been overused 6 , 28 , 29 . For this reason, it must be understood that many severe trauma patients may not require Damage Control Surgery, and may undergo definitive laparotomy during their initial intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Una vez se hayan alcanzado los objetivos principales de la cirugía de control de daños, se deben enfocar los esfuerzos por proveer la corrección del rombo letal y solo cuando se logre una adecuada resucitación se podrá realizar un manejo quirúrgico definitivo. En una reciente revisión de Cochrane se informó que la apropiada selección de los pacientes que se benefician de la estrategia de control de daños depende en alta medida del juicio médico y aunque se ha demostrado que esta estrategia aumenta la sobrevida de los pacientes politraumatizados, también se ha constatado que ha sido sobre utilizada 6 , 28 , 29 . Por esta razón, es importante que el cirujano esté consciente que no todos los pacientes de trauma requieren un control de daños y en muchos de ellos se puede realizar como primera intervención un control definitivo.…”
Section: Discussionunclassified
“…In the presence of vascular compromise, the devitalized bowel must be resected and intestinal continuity must be reestablished with anastomotic sutures. Otherwise, if the adjacent bowel is found to be viable, the mesentery tear must be closed with sutures and not ligated, as it could potentially herniate [14,15].…”
Section: Discussionmentioning
confidence: 99%